Consumer Activism and Its Consequences: Analyzing the Impact of Boycotts on Brand Reputation and Loyalty in Malaysia - Anees Jane Ali; Ainul Mohsein Binti Abdul Mohsin; Muhammad Muhaimin Afif bin Muhsin; Muhammad Ilham Bin Mohamad Nizam; Muhammad Shamim Bin Azirul Rahman; Muhammad Shamsul Hakimy Bin Mohd Saidin; Naginesne A/P Ganesan; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
McDonald’s is one of the world’s leading fast-food chains that has been a prominent player in Malaysia since 1982. With over 300 outlets in Malaysia, McDonald’s serves millions of customers emphasizing convenience, quick service and digital innovations. Despite its popularity, McDonald’s has faced periodic challenges including consumer boycotts caused by various reasons. This paper analyzes the impact of boycotts on McDonald’s in Malaysia aiming to understand the motivations behind these actions and their effects focusing on consumer boycotts action, corporate image and reputation, social media amplification, consumer loyalty and perceived performance. By utilizing a quantitative approach involving 102 customer surveys, this study investigates the impacts of boycotts on its public image. The survey results reveal that consumer boycott actions significantly influence brand reputation and consumer loyalty with socio-cultural factors in Malaysia amplifying their impact. This finding offers valuable insights into how consumer activism works and how McDonald’s responds to the impact of boycotts in influencing business practices.